Study of F1 car aerodynamics front wing using computational fluid dynamics (CFD) - Mohd Syazrul Shafiq, Saad (2010)
The aim of this thesis is to analyze a basic front wing of a typical Formula One car using Computational Fluid Dynamics (CFD). Commercial software Gambit and Fluent was used in this CFD analysis and Solid Works as tool for designing the front wing. The front wing is crucial in term of its influence on the handling and dynamics of the car and efficiently directing the flow to other parts of the car. Design used for the front wing is based on NACA 23012, based on research from Freddie Mehta (2006). The validation study show that CFD capable of predicting the CL with sufficient refine mesh and turbulence model assumptions. Turbulence model used in this analysis is Spalart- Allmaras turbulence model. CL value for inverted NACA 23012 is -0.24,-0.49, -0.67, and -0.80 for angle of attack 20,40,60, and 80 respectively. For CD is 0.06,0.07,0.09, and 0.12 for angle of attack 20,40,60, and 80 respectively. While for multiple wing CL is -1.5 and CD is 0.26. All the analysis was run around 90000 numbers of cells at interval size 5. The CL values were approximately matched with the experimental result.